Beyond hybrid professionals: evidence from the hospital sector - Marco Sartirana (BMC, 2019)
Abstract Background The involvement of doctors in managerial roles seems to be the solution to reducing the friction between traditional professionalism and modern organizational paradigms. However, these "hybrid" professionals responded in different ways to these conflicting demands, and we need to better understand the contextual factors that explain such variation. Methods The paper studies hybrid professionals in a hospital characterized by numerous organizational changes. The site is located in Italy, a country in which healthcare organizations have been exposed to managerial reforms for years but where the degree to which professionals embraced management varies. A longitudinal case study was performed that involved gathering data through multiple sources of evidence to understand the complex organizational dynamics that take place in the hospital. Results The analysis shows that the taking up of hybrid managerial roles is enabled by a number of interrelated features of the social/organizational context. Professionals willing to become hybrids were favored by the support provided by the organization. While for those doctors initially more reluctant towards medical management, distinctive contextual factors, in particular, the presence of space for interaction with colleagues within the professional domains but beyond disciplinary boundaries, was of key importance. This second group also proved capable of interiorizing organizational values and practices in a reconfigured way. Conclusions In order to understand hybridization, it is necessary to look beyond hybrids at the context surrounding them. This study provides evidence for scholars and practitioners willing to understand how medical management is evolving and how this transition can be supported, and it contributes to the literature on hybrid managers by showing how contexts facilitating social interactions enable professionals' hybridization. Trial registration The article does not report the results of a health care intervention on human participants, and material used in the research did not need ethical approval according to Italian law.